PEMANFAATAN MUSEUM NEGERI âBALANGAâ SEBAGAI MEDIA PEMBELAJARAN DI KALIMANTAN TENGAH - Azis, Abdul (Jurnal Studi Agama dan Masyarakat, 2013)
Everything that mediates learning is it in the form of objects, people, environments, or experiences that contain the value of learning and to stimulate the studets for learning, include, learning media. State Museum "Balanga" in Kota Palangka Raya, the capital of the Province of Central Kalimantan is one of the media that can be used for the importance of learning by the students. The museum seems to have been used, but if viewed in terms of intensity and volumes as well as visitors are not yet up as expected. It can be seen from the intensity and the number of visitors who are still relatively few and visitors who come to the museum, many of them just simply for recreation and streets not only in order to study activity.